Cantillever based MEMS pressure sensor - Siva Kumar, M.; Srinivas Rao, K.; Kumar Tulas, Sanath; Prasad, G R K; Hari Kishore, K (International Journal of Engineering and Technology, 2017)
Objective: We are analyzing the different piezoelectric materials which are best sutable combination for the design of pressure sensors used for the production of voltage.Our main theme is to find which combination gives high voltage.Methods:We are incorporating different layers on the cantilever beam such as piezoelectric material (PZT,BaTiO3), electrode(Pt,Al), insulator(Si3N4) on siliconwafer(SiO2). We had used these materials for MEMS pressure sensor utilizing diverse [different] Piezoelectric materials The relative study by simulation can be utilized to give the rules to a configuration and streamlining of execution of the distinctive piezoelectric micro cantilever pressure sensors.Findings:.We have designed, displayed and simulated our module in COMSOL software taking into account limited component strategy [FEM]. The structure made up of silicon on piezoelectric micro cantilever with cantilever beam. In reenactment [simulation] we have concentrated on varying so as to displacement and voltage connected pressure. It is observed that the induced voltage is practically straight [linear] with the applied forceImprovement:From this design we analysed that at particular dimensions of materialswithcombinationofPZTand Al gives best voltage than remaining combinations like PZT and Pt.